El cuidado transicional de enfermería aumenta la compentencia en el rol del cuidador del niño con cáncer - Carreño Moreno, Sonia (Psicooncología, 2017)
Introduction. The family caregiver of child with cancer goes through a transition in their role in strengthening competence required to exercise it.Objective. To determine the effect of an intervention of transitional nursing care on the competency of the family caregiver of a child with cáncer. Methodology. Experimental study, the experimental group (n=59) underwent an intervention developed by the investigators “Taking care of our children with cancer”, the control group (n=59) received usual care. It was measured the competency of care of the caregiver, it was a double-blind study. The analysis was performed using the Student’s t test, the effect size was estimated using average exchange standardized difference - d Cohen.Results. Most of the children were diagnosed with leukemia 41% and the average age was 4 years. Family caregivers are women 84%, mean age 33. A competency of care difference (p
Keywords: Family caregivers; child care; oncology nursing; health transition.